Break up with narcissism : how to break free and stay free - Kastner, Alina (Fair Winds Press, an imprint of The Quarto Group, 2026)
"Break Up with Narcissism by leading expert and social media influencer, Dr. Alina Kastner, offers a four-step plan for recovering from narcissistic relationships"-- Provided by publisher.